EMERGING SUBJECTIVITY AND MEANING WITHIN THE LABOR PROCESS OF INDIAN INFORMATION TECHNOLOGY - Joshi, Chandra Shekhar (PEOPLE: International Journal of Social Sciences, 2020)
The limitless possibility of ‘being’, whatever one wants ‘to become’ in the contemporary ‘liquid modern times’ inherently accentuates complexities and ambiguities (Bauman 2000) in the ‘conceptualization of self’. Rather than offering conduit for fulfillment and stable anchoring for personal identity (Alvesson and Willmott 2002), work in the new economy and corresponding altered employment relations, seem to impose corporate narratives of ‘how one ought to be’. Resulting identities warrant for continuous identity work and thus aggravate perpetual feelings of insecurity and anxiety (Collinson 2003). In absence of traditional anchors of meaning (Sennett 1998) and corresponding unrealized quest for alternative forms of attachment and belonging (Jackall 1998), subjectivities at work are precarious at the very least. Given the context, the paper interrogates worker subjectivity within the labor process of Indian Information Technology (IT) to delineate meaningful work experiences for employees. The findings explicated from ethnographic field work indicate that despite significant contribution to the Indian economy and catapulting sizeable number of families into higher social strata, the software economy has also resulted in what has been described as ‘deteriorating culture’ by most of the respondents. Unsurprisingly, transactional employment relationships, eroding mutual trust and individual predisposition to self-securing orientation have been found to be prominent characteristics of Indian IT workplaces. It seems that contradictions inherent in the individualization oriented IT labour process in a quasi-collectivistic society such as India erodes the capacity of work in providing salient identity dimensions to its employees. Interestingly, the findings from the field also indicate that work itself has no meaning but it is the instrumentality of work in achieving other life projects, particularly those associated with positive valence in the society which makes work experience as meaningful or meaningless.